Analisis Penerapan Blockchain Untuk Keamanan Data Medis Elektronik - Bella Gusmita Sari; Diki Ananda; Anisa Dwi Arianti; Indra Gunawan (PT Siantar Codes Academy Publisher, 2025)
The digital transformation in healthcare has introduced both opportunities and challenges, particularly in managing the security and privacy of electronic medical records (EMR). Medical data is highly sensitive and valuable, making it a prime target for cyberattacks, data breaches, and unauthorized manipulation. Blockchain technology has emerged as a promising solution to strengthen the security, integrity, and transparency of medical data management.This study aims to analyze the potential implementation of blockchain in protecting electronic medical data through a literature review of scientific articles, conference proceedings, white papers, and industry reports published between 2016 and 2024. The findings indicate that blockchain provides distributed encryption mechanisms, consensus-based authentication, and immutable transaction records. These features not only reinforce data security but also enhance trust among patients, healthcare professionals, and institutions.